Hubungan Asupan Energi, Zat Gizi Makro, dan Aktivitas Fisik terhadap Status Gizi pada Remaja MA Annajah - Vivi Putri Rahmadani; Ratu Diah Koerniawati; Annisa Nuradhiani (Tirtayasa Medical Journal, 2026)
Adolescents are a vulnerable group to nutritional problems. The prevalence of adolescents aged 16-18 years who experience nutritional problems based on BMI/U parameters is very thin (2.6%), thin (5%), overweight (14.4%), and obesity (4.8%). The vulnerability to nutritional problems in adolescents can be caused by direct factors (type of food consumed, including energy and macronutrient intake) and indirect (physical activity). The purpose of this study was to analyze the relationship between energy intake, macronutrient intake, and physical activity with the nutritional status of adolescents. This study used an observational analytical design with a cross-sectional approach. This study was conducted at Madrasah Aliyah Annajah with a sample of 78 people selected using a purposive sampling method. Data collection was carried out by filling out the Physical Activity Level (PAL) questionnaire, interviews using a 3x24-hour food recall questionnaire (2 weekdays and 1 holiday), and direct measurement of height and weight. Data were then analyzed using the Fisher's Exact test. The results of the study showed that most respondents had sufficient energy intake (43.6%), excess protein intake (43.6%), excess fat intake (60.3%), insufficient carbohydrate intake (73.1%), and light physical activity levels (94.9%). Some respondents' nutritional status was still abnormal, consisting of obesity (19.2%), overnutrition (16.7%), and malnutrition (3.8%). There was a significant relationship between energy, protein, fat, and carbohydrate intake with nutritional status (0.000; 0.000; 0.000; 0.000), but there was no significant relationship between physical activity and nutritional status in MA Annajah adolescents (0.534).